Pemanfaatan Digital Marketing Dan Pengembangan SDM untuk Meningkatan Kualitas Pelayanan Akomodasi di Desa Wisata Taro Tegallalang Gianyar Bali - Kalpikawati, Ida Ayu; Sulistyawati, Ni Luh Ketut Sri; Pinaria, Ni Wayan Chintia; Adinda, Clearesta; Suastini, Ni Made; Loananta, Cahyo Purnomo; Pratiwi, Kadek Andita Dwi; Jata, I Ketut (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Taro Village is one of the leading tourist villages in Gianyar, Bali, offering natural and cultural potential that supports community welfare through tourism. By 2024, there has been a significant increase in the number of accommodations in Taro Village, which has created new challenges regarding digital marketing and meeting service standards in accommodation management. This Community Service Program aims to enhance the competence of accommodation managers in Taro Village through training on excellent service, accommodation standardization, and effective digital marketing. The program combines socialization and practical activities, focusing on improving accommodation visibility as well as implementing service standards and processes. The expected outcomes include enhanced competence of accommodation managers, a deeper understanding of digital marketing, and better service standard implementation, enabling Taro Village to compete as a premier tourist destination. The program was attended by 30 participants, including accommodation owners, members of Pokdarwis, and local residents involved in the tourism sector in Taro Village. The activities, consisting of socialization and practical sessions, were held on September 17-18, 2024. The evaluation was conducted by distributing questionnaires to participants to measure their satisfaction. The results showed that the average satisfaction score reached 3.8, which falls into the